Biarum persicum, a new species from Iran, and the resurrection of Biarum platyspathum (Araceae) - Ali̇pour, Sajad; Maji̇di̇, Rami̇ar; Balos, Mehmet Maruf (Phytotaxa, 2025)
In this study, Biarum persicum is described as a new species from Iran. It is similar to Biarum carduchorum, but differs mainly by its tuber structure, leaf structure, spathe shape and length, spadix length, ovary and fruit structure. Moreover, the taxonomic status of Biarum platyspathum, which was considered as a synonym of of Biarum carduchorum in previous studies, has been re-evaluated based on morphological studies. Biarum platyspathum is morphologically similar to Biarum aleppicum and B. carduchorum. However, it is noted that Biarum platyspathum differs mainly by its cataphyll structure, number of leaves, spathe structure, spadix structure, ovary structure, fruit and seed structure from both taxa. A comprehensive account is provided for the newly described and resurrected species, including diagnostic characteristics, photographs, geographical distribution, conservation assessments, relevant observations, and a distribution map.